Reconceptualizing English Grammar Instruction in Secondary School: A Flipped Classroom Approach to Enhancing Student Participation - Maruf, Nirwanto; Khalil, Morve Roshan; Aeni, Nurul (JET ADI BUANA, 2026)
This study examined the use of the flipped classroom model to enhance student participation in secondary school English grammar lessons and explored students’ perceptions of its implementation in grammar learning. The study was motivated by the persistent problem of low participation in grammar instruction, which is often characterized by teacher-centred explanation, limited interaction, and students’ low engagement. To address this issue, the study employed a Classroom Action Research design conducted in two cycles over eight weeks. The participants were 30 eighth-grade students from a public secondary school in Indonesia. Data were collected through a structured observation checklist, student participation logs, a questionnaire, semi-structured interviews, and a reflective journal. Quantitative data were analysed using descriptive statistics, while qualitative data were analysed thematically. The findings showed that the flipped classroom model was associated with a clear improvement in student participation across the two cycles. Access to pre-class materials increased from 70% in Cycle 1 to 93% in Cycle 2, while readiness for in-class discussion improved from 55% to 85%. Engagement in collaborative tasks rose from 60% to 90%, and responses to teacher prompts increased from 50% to 80%. Questionnaire results also indicated generally positive student perceptions. Most students agreed that the pre-class materials helped them understand grammar concepts, increased their confidence in classroom participation, and made grammar learning more engaging. However, some students reported difficulties related to self-regulated learning and limited internet access. The study concludes that the flipped classroom model can serve as a productive pedagogical approach for reconceptualizing grammar instruction in secondary school by promoting more active, participatory, and interaction-rich learning. The findings also suggest that the effectiveness of the model depends on careful instructional design and adequate support for students’ pre-class learning.